If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12y + 4(90 + -3x) = 360 12y + (90 * 4 + -3x * 4) = 360 12y + (360 + -12x) = 360 Reorder the terms: 360 + -12x + 12y = 360 Add '-360' to each side of the equation. 360 + -12x + -360 + 12y = 360 + -360 Reorder the terms: 360 + -360 + -12x + 12y = 360 + -360 Combine like terms: 360 + -360 = 0 0 + -12x + 12y = 360 + -360 -12x + 12y = 360 + -360 Combine like terms: 360 + -360 = 0 -12x + 12y = 0 Solving -12x + 12y = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12y' to each side of the equation. -12x + 12y + -12y = 0 + -12y Combine like terms: 12y + -12y = 0 -12x + 0 = 0 + -12y -12x = 0 + -12y Remove the zero: -12x = -12y Divide each side by '-12'. x = y Simplifying x = y
| x^(4/3)=2x^(1/3) | | x^(8/7)=6x^(1/7) | | 4(1+0.75y)-8=3y-4 | | 12w^2+15w^3= | | 5(s-2)=3(x+4) | | 1104=3*2*D | | √3/3=120√3/x | | 5(x-2)=20-x | | 25.00-x=3.45 | | y=4x^2+16x+64 | | -2/4= | | 2x+26y=21y+3x | | V=(10)(8)(5) | | 9x^2+y^2=16 | | 2(s+11)=5(s+12) | | 7x-5.5=4x+11 | | 2a+9=1 | | (x+1)2=x+7 | | 2x-3x(23y)=15x | | -2.5x+4.3x=-2.5-2.3 | | .376=3/8 | | 3.2=5.7a-4.7a-9.2 | | n-5.1=-6.8 | | 25x/100*110 | | (x+y)(x-y)=48 | | 5(x-1)=3(x-4)+66 | | 5(x-1)=3(x-4)+6 | | -5.6+3.2=9.6z-8.6z-.2 | | .1=1.8z-.8z+8.9 | | n+5.6=-8.8 | | x-2.8=-6.9-1.4 | | 5x^2+30x=-65 |